Study on the Community Satisfaction Index (CSI) to Realize Excellent Public Services - Solihin, Ihin; Hendarso, Panji; Sonjaya, Trisna; Latifah, Eva; Dharmawan, Awan; Yudistira, Yudi (Jurnal Manajemen Pelayanan Publik, 2026)
This study is purposed to examine the quality of public services as measured by the Monitoring and Evaluation of Public Service Performance (PEKPP), sourced from the Community Satisfaction Index (IKM) during the period 2022-2024 across all regions of Indonesia. This study is a literature review based on secondary data with a qualitative descriptive approach. The results of the study indicated that the quality of the Community Satisfaction Index (IKM), oriented towards excellent public service in all regions of Indonesia, demonstrated improvement; however, it has not shown significant quantitative progress. The recommendation for this study is that the government should take effective steps to increase the number of regions categorized as regions with excellent public services.